Ante Šiljeg, PhD in Interdisciplinary Sciences - Sanja Lozić (Kartografija i Geoinformacije, 2013)
Ante Šiljeg defended his doctoral thesis The Digital Relief Model in Analysis of Geomorphometric Parameters – Example of PP Vrana Lake at Faculty of Science, University of Zagreb on June 20th, 2013 (supervisor Sanja Lozić, PhD, assistant professor) and received a PhD degree in the field of interdisciplinary science, field of geography, branch of applied geography. Doctoral thesis was defended in front of committee composed of Mladen Pahernik, PhD, assistant professor, Danijel Orešić, PhD, associate professor and Aleksandar Toskić, PhD, associate professor. Commitee for disertation review was in the same composition.